Ultrafast all-optical switching of germanium-based flexible metaphotonic devices - Lim, Wen Xiang (2019)
Incorporating semiconductors as active media into metamaterials offers opportunities for a wide range of dynamically switchable/tunable, technologically relevant optical functionalities enabled by strong, resonant light–matter interactions within the semiconductor. Here, a germanium‐thin‐film‐based flexible metaphotonic device for ultrafast optical switching of terahertz radiation is experimentally demonstrated. A resonant transmission modulation depth of 90% is achieved, with an ultrafast full recovery time of 17 ps. An observed sub‐picosecond decay constant of 670 fs is attributed to the presence of trap‐assisted recombination sites in the thermally evaporated germanium film.